ANALISIS SEGMENTASI, TARGETING DAN POSITIONING PT SENTUL CITY TBK - Lestari, Ayu Ria; Purnamasari, Oktaviana (Prodi Ilmu Komunikasi Universitas Putera Batam, 2025)
This study aims to explore the segmentation, targeting, and positioning strategies at PT. Sentul City, Tbk. Using a qualitative approach, the research gathered information through in-depth interviews with relevant informants. The findings reveal that Sentul City adopts a structured approach to determining target segments, considering characteristics such as age, profession, and lifestyle preferences. The company's primary targets encompass various groups, ranging from private employees, civil servants, property investors, entrepreneurs, and retirees. In the positioning strategy, PT. Sentul City emphasizes the creation of elegant, minimalist, and classy property environments to meet the needs of consumers seeking a modern lifestyle. The properties are designed to reflect status and aspirations for living in a high-quality environment. By utilizing the online platform, the company ensures the availability of comprehensive information and facilitates interaction with potential buyers. This research provides in-depth insights into how PT. Sentul City formulates and implements its property marketing strategies, serving as a valuable reference in the property industry.